Member's retention in fitness: contribution of the quality of services, expectations, satisfaction in life and in the club - Gonçalves, Celina (2019)
Members retention is essential for financial viability of fitness organizations. Thus, these organizations focus on service quality to keep their members satisfied (Lee, Kim, Ko, & Sagas, 2011) and to maintain or exceed their expectations (Robinson, 2006; Pedragosa, & Correia, 2009). Therefore, gyms and health clubs expect that satisfied members repurchase and spend extra money in their fitness services (Ferrand, Robinson, & Valette, 2010) increasing organization profitability. In this study, it was intended to understand the contribution to the members’ retention intention in fitness organizations regarding: service quality; expectations; satisfaction in life; and satisfaction in the club.